Exploring Barriers and Enablers for Women Entrepreneurs in Urban Ireland: A Qualitative Study of the Greater Dublin Area - Marcus Goncalves; Megan Trainor; Andreana Ursini (Social Sciences)
This research investigates the pivotal role of women’s entrepreneurship in urban Ireland. Utilizing a demand–constraint–choice framework for analysis, it explores the diverse motivations behind Irish women’s entrepreneurial ventures, emphasizing the impact of time- and place-specific factors. The study also assesses gender equality and disparities. This qualitative research presents a comparative analysis of motivations, perceptions, and experiences conducted through semi-structured interviews in Ireland’s diverse cultural and economic contexts. The findings highlight the influence of cultural factors on women’s entrepreneurial choices and the significance of government support systems. They underscore the necessity of proactive government intervention for gender-inclusive economic development, offering insights applicable beyond Ireland. Valuable for policymakers, researchers, and entrepreneurs, the findings enhance understanding of women’s entrepreneurial leadership, contributing to global strategies for empowering women in entrepreneurship. Several policy recommendations are provided.